2008
DOI: 10.1108/17410400810857266
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the effectiveness of the balanced scorecard with scenario planning

Abstract: Purpose -This paper aims to propose the idea of linking the use of the balanced scorecard with scenario planning. Scenario planning emphasizes the development of a strategic plan that is robust across different scenarios. This ensures that the strategy implemented using the balanced scorecard is linked to external conditions and takes into consideration the expected changes in the environment. Design/methodology/approach -This paper examines the criticisms of the balanced scorecard and proposes the use of scen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 24 publications
0
32
0
Order By: Relevance
“…Typically, in many organisations, there are inconsistencies in the frequency of gathered values and the range in which the values vary over a period of time. Othman (2007) argues that a very serious drawback of strategy maps is the lack of representing the time evolution element in strategic plans. This missing time element also influences the ability to model performance indicators in SMs.…”
Section: Need For Fuzzines In Causal Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, in many organisations, there are inconsistencies in the frequency of gathered values and the range in which the values vary over a period of time. Othman (2007) argues that a very serious drawback of strategy maps is the lack of representing the time evolution element in strategic plans. This missing time element also influences the ability to model performance indicators in SMs.…”
Section: Need For Fuzzines In Causal Relationshipsmentioning
confidence: 99%
“…Even though the literature on strategy mapping is fairly vast, few authors have suggested the combination of strategy maps and scenario analysis (Fink et al, 2005;Othman, 2007) and none of them has described the actual design process and nobody using any tools with simulation capabilities.…”
Section: Scenario Based Strategic Mapsmentioning
confidence: 99%
“…For example, the awareness and capability building goal of CSS might have several sub goals being executed by different entities; national TV will run an awareness campaign for citizens, a security company will train professionals on how to prevent email attacks, another campaign will be conducted online to get e-commerce users be aware on how to prevent credit card frauds, etc. Our proposed Holistic BSC helps in solving the problems pointed out by [24] and [23].…”
Section: Proposed Modelmentioning
confidence: 99%
“…It is built for the level of an organization and below. Moreover, the BSC is "seen as myopic and ignores the activities and initiatives that goes beyond the original targets" [23]. Furthermore, the BSC can point out problems but not how to reveal them [24].…”
Section: Information Technology Security Balanced Scorecardmentioning
confidence: 99%
“…[8] developed a called "future scorecard" in which some consideration is given to the possibility of developing a scorecard that possesses an additional input with the information and conclusions derived from environmental analysis. On the other hand, Othman [9] establishes that a balanced scorecard could be linked with scenario planning by taking into account a future state or scenarios to be reached when formulating the PMS strategy. Both of these works are theoretical and do not go beyond, as they neither propose a structured method nor provide experiences derived from application.…”
Section: Scenario Planning and Performance Measurementmentioning
confidence: 99%